2021
DOI: 10.1371/journal.pone.0233243
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of stimulating multiple body parts simultaneously to the illusion of owning an entire artificial body

Abstract: The full-body ownership illusion exploits multisensory perception to induce a feeling of ownership of an entire artificial body. Although previous research has shown that synchronous visuotactile stimulation of a single body part is sufficient for illusory ownership of the whole body, the effect of combining multisensory stimulation across multiple body parts remains unknown. Therefore, 48 healthy adults participated in a full-body ownership illusion with conditions involving synchronous (illusion) or asynchro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 83 publications
(197 reference statements)
2
15
0
Order By: Relevance
“…The differences between body parts and the whole body have been examined, and neuroimaging studies examining their visual representation have shown that information about body parts and the whole body are represented in separate neural bases ( Taylor et al, 2007 ; Brandman and Yovel, 2016 ). The RHI and FBI also differ in terms of the onset time of the illusions: in the RHI, the onset time is less than 15 s ( Lloyd, 2007 ), whereas in the FBI, the onset time is 28 s—a difference of about 10 s ( O’Kane and Ehrsson, 2021 ). Although the reason for this difference has not yet been clearly examined, it is possible that the larger the target of the manipulated sense of body ownership, the longer it takes for the illusion to be generated.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between body parts and the whole body have been examined, and neuroimaging studies examining their visual representation have shown that information about body parts and the whole body are represented in separate neural bases ( Taylor et al, 2007 ; Brandman and Yovel, 2016 ). The RHI and FBI also differ in terms of the onset time of the illusions: in the RHI, the onset time is less than 15 s ( Lloyd, 2007 ), whereas in the FBI, the onset time is 28 s—a difference of about 10 s ( O’Kane and Ehrsson, 2021 ). Although the reason for this difference has not yet been clearly examined, it is possible that the larger the target of the manipulated sense of body ownership, the longer it takes for the illusion to be generated.…”
Section: Discussionmentioning
confidence: 99%
“…The recordings from the left and right cameras were placed next to one another on the HMD screen (1920 x 1080 pixels) such that footage from the left camera was sent to the left half of the screen and footage from the right camera was sent to the right half of the screen. Throughout each video, a white Styrofoam ball (6.5 cm in diameter) attached to a wooden stick (1 m long) repeatedly stroked the mannequin’s torso from the sternum to the belly button in a downwards direction every 2 seconds for 40 seconds total ( O'Kane and Ehrsson, 2021 ). Each stroke lasted approximately 1 second.…”
Section: Methodsmentioning
confidence: 99%
“…Some allowed finger movements of the rubber hand (e.g., Kalckert and Ehrsson, 2012), which adds the possibility to test for agency. Currently, more studies on embodiment are run in VR (e.g., Kilteni et al, 2012b;O'Kane and Ehrsson, 2021), thereby providing more flexibility and the opportunity to test conditions where the position of the virtual and the real arm overlap (c.f., Ma et al, 2021), which was impossible with the original RHI setup.…”
Section: Previous Work On Embodiment and Presence Frameworkmentioning
confidence: 99%